The promotion of mental health of adolescents in a township in Swaziland - J.S. Siphepho; A.C. Gmeiner (AOSIS, 2000)
A number of adolescents have been observed drinking alcohol, pushing and abusing drugs and also stealing cars. A lot of adolescents idle in the township streets, girls are falling pregnant and dropping out of school. No research has been done to elicit the opinions of families on the everyday life of the adolescents in this township. The objectives of this research were twofold, namely: To explore and describe the families' opinions on the everyday life of adolescents in a specific township in Swaziland, and to describe guidelines for advanced psychiatric nurse practitioners to assist these families to mobilize resources in order to promote, maintain and restore mental health as integral part of health of adolescents in this township. A qualitative, exploratory, descriptive and contextual design was used where the research was conducted in two phases. Trustworthiness measures as well as ethical measures were applied throughout the research. Five categories were identified from the result of the focus group interviews with families: Adolescents presenting ineffective communication patterns due to lack of support from their families; adolescents engaging into risky lifestyles related to lack of support and healthy relationships with their parents; families unable to create a supportive and conducive environment for their adolescents due to their focus on own family stumbling blocks and non-availability of recreational centres related to lack of a supportive and conducive environment in the community and inadequate accommodation leading to overcrowding. Guidelines for advanced psychiatric nurse practitioners were deducted from identified themes and the literature control.